Decoding neutrophil extracellular traps and key gene drivers in unexplained pregnancy loss - Ding, Hui; Zhang, Lu; Yang, Wei; Liu, Yu; Wang, Chao; Liu, Li; Li, Cheng; Pan, Liyuan; Chen, Lin; Liu, Meimei (Frontiers in Immunology, 2025)
BackgroundRecurrent pregnancy loss (RPL) represents a critical reproductive health concern, with nearly half of RPL cases lacking clinically identifiable etiologies, termed unexplained RPL (uRPL). Neutrophil extracellular traps (NETs), released by activated neutrophils, have been implicated in the pathogenesis and progression of various reproductive disorders. However, the relationship between NETs and uRPL remains poorly characterized.MethodsThis study enrolled 34 patients with uRPL and 30 healthy controls. Serum NETs biomarkers (MPO-DNA, citH3) were quantified via ELISA. Decidual tissues underwent histopathology (H&E), immunohistochemistry, and transcriptomics (6uRPL vs. 5 controls). Machine learning identified key NETs-related differentially expressed genes, validated by Western blotting. Immune cell infiltration and gene-immune correlations were assessed bioinformatically.ResultsuRPL patients exhibited elevated serum NETs biomarkers (MPO-DNA, citH3; p<0.01) and increased decidual neutrophil infiltration. Immunohistochemistry confirmed upregulated MPO and citH3 in uRPL (p<0.01). Transcriptomics identified four key DE-NRGs (C3AR1, ITGAM, ITGB2, LYZ), validated at the protein level (p<0.05). Immune profiling revealed increased CD8+ T cells, M2 macrophages, and neutrophils, alongside reduced CD4+ memory T cells, follicular helper T cells, and monocytes in uRPL. All DE-NRGs correlated positively with M2 macrophages (r>0.6) and negatively with follicular helper T cells and monocytes (r<-0.5). LYZ also correlated with neutrophils (r>0.5). A nomogram incorporating DE-NRGs demonstrated robust diagnostic accuracy (AUC>0.85).ConclusionThis study establishes a novel link between NETs and the pathogenesis of uRPL. It highlights the abnormal activation of C3AR1, ITGAM, ITGB2, and LYZ, along with M2 macrophage polarization, as crucial factors in decidual immune dysregulation. These findings suggest that NETs could serve as therapeutic targets, while DE-NRGs may act as potential biomarkers for uRPL.